Estudo da validade de generalização das práticas de governança corporativa ao ambiente dos fundos de pensão: uma análise segundo as teorias da agência e institucional - Fontes Filho, Joaquim Rubens (2004)
The research aimed at analysing the political and discursive practices of the metanarrative of employability in the contemporary organizational field, heading for the understanding of the social and micropolitical devices which happen to produce some especific kinds of subjectivities within organizations. From a post-modern epistemological perspective (Weltanshauung), the research focused on the issues concerning the production of subjectivities in the existing organizational society beyond the traditional theoretical standpoints whose common assumptions are due to the modernist approaches of organizational analysis. A deconstructive theoretical approach was emphasized across the whole text and it was mainly inspired and intellectually based upon Michel Foucault's genealogical démarche. His original conceptualization of power-knowledge relations informed the development of a methodology so as to analyse the discursive practices which determine many of the human resources policies concerning employability. The main thesis presented employability as a grand-device of micropolitical control towards the production of subjectivities whose main operation technologies are: an economic modernizing rhetoric, a moralistic dietetics and an instrumental education. Several discursive fragments from different academicists, journalists and some authors from the managerial litterature were taken into account so as to carefully deconstruct their speeches. This analysis revealed the mechanisms of production of pasteurized, mercantile and erratic subjectivities. Some inquietudes of heuristic nature are featured in the domain of organizational, psychological, sociological and political perspectives heading for new studies.